A case of complete atrioventricular block in secondary hemophagocytic syndrome/hemophagocytic lymphohistiocytosis recovered by plasma exchange and cytokine absorbing therapy with AN69ST continuous hemodiafiltration. Issue 4 (1st October 2020) - Harano, Yoshihiro; Ishikawa, Yuichi; Hattori, Koto; Ichinose, Mami; Tomofuji, Yoshihiko; Okano, Hiroshi; Owada, Gen; Kimura, Yasuhiro; Nanao, Taikan; Fujimoto, Junichi; Nishizawa, Hideo; Iioka, Yuto; et al.
Abstract: We report a case of incipient systemic lupus erythematosus (SLE) that rapidly progressed to complete atrioventricular block (cAVB). A 20-year-old man was admitted with facial erythema, painless oral aphtha, polyarthritis, and myalgia of each extremity. On admission, he developed first-degree atrioventricular block, pericarditis, pleuritis, renal failure, hemophagocytic lymphohistiocytosis, neurophychiatric SLE (left cerebellar infarction), and Staphylococcus aureus bacteremia. He was subsequently diagnosed with SLE based on several positive findings on immunological tests (including positive for antinuclear antibody). Despite immediate glucocorticoid pulse therapy and plasma exchange (PE) along with antibiotic, he developed cAVB that required temporary pacing on day 2. Because it was thought that hypercytokinemia exacerbated pericarditis, which progressed to myocarditis and cAVB, we decided to PE and cytokine-adsorbing therapy with AN69ST-continuous hemodiafiltration (CHDF). Other than renal failure, his organ dysfunctions improved with the multidisciplinary therapy. CAVB improved and temporary pacing was no longer required on day 11. Even a first-degree atrioventricular block can rapidly progress to cAVB; therefore, strict attention to electrocardiogram is necessary in severe SLE cases. When presenting with organ dysfunctions caused by hypercytokinemia such as severe SLE cases or SLE with severe infection cases, use of the combination of PE and AN69ST-CHDF might be beneficial.